Expression and clinical significance of Cathepsin K and MMPs in invasive non-functioning pituitary adenomas - Liu, Hongyan; Zhang, Saichun; Wu, Ting; Lv, Zhaohui; Ba, Jianming; Gu, Weijun; Mu, Yiming (Frontiers in Oncology, 2022)
Purpose Cathepsin K, one of the lysosomal cysteine cathepsins, degrades type I collagen and contributes to bone resorption. Some pituitary adenomas (PAs) invade the sphenoid sinus (SS) and cavernous sinus (CS). The aim of this study was to explore the expression and clinical significance of Cathepsin K and to investigate the differences in the expression of MMP-9, MMP-2, TIMP-2 and PTTG1 between SS-invasive and CS-invasive PAs. Methods Case-control study is used in our study. By collecting SS invasive PAs, CS invasive PAs and non-invasive PAs, the protein level of Cathepsin K, MMP-9, MMP-2, TIMP-2 and PTTG1 are investigated with Immunohistochemical staining procedure (IHC). Results We found that the levels of Cathepsin K were higher in PA cases with SS invasion than that in PA cases with CS invasion (95.57 ± 4.76 vs. 65.29 ± 4.19, P < 0.001), and the expression of MMP-9 and MMP-2 was higher in CS-invasive cases than that in SS-invasive cases (145.02 ± 6.97 vs. 111.80 ± 7.74, P = 0.002, and 138.67 ± 7.36 vs. 108.30 ± 5.94, P = 0.002). Patients with high Cathepsin K had a higher risk of recurrence (HR: 2.217, CI: 1.223-4.019, p=0.009). A positive correlation was observed between Cathepsin K expression and tumor size (r=0.671，p<0.001). There was no significant difference in TIMP-2 and PTTG1 levels between CS-and SS-invasive cases (97.99 ± 6.30 vs. 107.47 ± 6.51, P = 0.30 and 13.26 ± 0.46 vs. 12.86 ± 0.72, P = 0.63). Conclusion Our data indicate that Cathepsin K has a potential as a marker for SS invasion of PAs, whereas MMP-9 and MMP-2 may be markers for CS invasion. And Cathepsin K may play an important role in tumor relapse.